Total Synthesis of (−)‐Morphine. Issue 29 (25th April 2017) - Umihara, Hirotatsu; Yokoshima, Satoshi; Inoue, Masayuki; Fukuyama, Tohru
Abstract: Asymmetric total synthesis of (−)‐morphine has been accomplished in 18 steps from commercially available 7‐methoxy‐2‐tetralone. Our synthesis features a simple transformation from a readily prepared chiral intermediate, construction of the E‐ring by acid‐mediated cyclization, and singlet oxygen‐mediated manipulation of the C‐ring. Transformation of the final stage involves construction of the morphinan skeleton by means of 1, 6‐addition of in situ generated secondary amine. Abstract : Quick and painless : The asymmetric total synthesis of (−)‐morphine has been accomplished in 18 steps. Our synthesis features a simple transformation from a readily synthesized chiral intermediate, construction of the E‐ring by acid‐mediated cyclization, and singlet oxygen‐mediated manipulation of the C‐ring. The final stage involves construction of the morphinan skeleton by means of 1, 6‐addition of an in situ generated secondary amine.